2010
DOI: 10.11150/kansenshogakuzasshi.84.431
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Novel Influenza A Virus and Seasonal Influenza A (H1N1, H3N2) Viruses by Reverse Transcription-Loop-Mediated Isothermal Amplification (RT-LAMP)

Abstract: Reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay we developed detects novel influenza A (H1N1) of swine origin and seasonal influenza A (H1N1 and H3N2) viruses. Individual primer sets targeting the HA gene for novel H1N1, H1N1, and H3N2 were newly designed to specifically detect these subtypes. No cross-reactions occurred among novel H1N1, H1N1, and H3N2, and 7 respiratory viruses-influenza B virus, influenza C virus, adenovirus, respiratory syncytial virus, metapneumovirus, parainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…At a pH between 7 and 11, the dye is in its blue form in the absence of metal ions and turns to a bright purple when it forms a complex with magnesium (Skoog et al 2014). Until now, the use of ErioT in LAMP reactions was only rarely reported; however, Shigemoto et al (2010), Oh et al (2016), andRodriguez-Manzano et al (2016) demonstrated the suitability of ErioT for colorimetric detection in LAMP assays.…”
mentioning
confidence: 99%
“…At a pH between 7 and 11, the dye is in its blue form in the absence of metal ions and turns to a bright purple when it forms a complex with magnesium (Skoog et al 2014). Until now, the use of ErioT in LAMP reactions was only rarely reported; however, Shigemoto et al (2010), Oh et al (2016), andRodriguez-Manzano et al (2016) demonstrated the suitability of ErioT for colorimetric detection in LAMP assays.…”
mentioning
confidence: 99%
“…Our multiplex RT-LAMP detection system was designed to be a more feasible RIDT with accuracy as high as RT-PCR methods for detecting most recent human influenza viruses and avian influenza viruses infecting humans. Although a variety of reliable and affordable RT-LAMP methods have been developed to detect human or avian influenza viruses, each can only detect an individual subtype [23-29, 34, 35] or limited subtypes of human influenza viruses and/or avian influenza viruses infecting humans [18,30,36,37]. In a pandemic, it is critical to rapidly differentiate patients infected by seasonal flu from those infected by an emerging strain.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity and sensitivity of RT-LAMP are potentially comparable to those of existing PCR-based diagnostics with much shorter reaction time. Recently, influenza diagnostics tools leveraging RT-LAMP technology have been reported [23][24][25][26][27][28][29][30]. However, most of these tools can only diagnose a single or a small number of human influenza viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the cause of infection solely based on clinical parameters is quite impossible, while the treatment of viral and bacterial infections differs significantly. Assay requirements for viral diagnostics, such as sensitivity and the possibility High rate of false positives [11,12] NA, Not available; EID50, 50% egg infective dose -1 EID50 is the amount of virus that will infect 50% of inoculated eggs; VP, Virus particles; HAU, Hemagglutination units -1 HAU is the amount of virus needed to agglutinate an equal volume of standardized red blood cells. for multiplexing and quantification all depend on the purpose of the application.…”
Section: Requirements For Viral Diagnosticsmentioning
confidence: 99%